Vài ý kiến xung quanh việc xác định nguồn gốc, tên gọi, thành phần tộc người của người Chăm Hroi ở Bình Định và Phú Yên - Mai, Minh Nhật (Trường Đại học Đà Lạt, 2012)
In thí article, the author presents the opinions of some foreign and Vietnammes researchers about the origin, name and indentification of the Cham Hroi people who live in the southwestern of Binh Dinh Province and the northwestern of Phu Yen Province.